Recruitment and retention of information professionals: library leaders' perspectives in Pakistan. Issue 6 (2nd September 2019) - Warraich, Nosheen Fatima; Ameen, Kanwal; Malik, Amara
Abstract : Purpose: This study aims to highlight the issues and concerns specific to information professionals (IPs) in academic libraries of Pakistan. It identifies the problems that academic libraries face in attracting and hiring competent IPs along with the strategies to be used to recruit and retain them in the dynamic environment of academia. Moreover, it provides a list of required skills that employers would look for while hiring IPs in academic settings. Design/methodology/approach: Semi-structured interviews of 20 library leaders involved in hiring process were conducted from 16 public and private sector universities. Findings: Findings identified interpersonal skills as the most desired followed by the subject knowledge and IT orientation while hiring IPs for the present and foreseeable future. Good salary package, conducive work environment with opportunities for learning and continuing professional development and speedy promotion were significant perceived factors to attract and retain the talented professionals in university library settings. Practical implications: The study would be helpful for policymakers and administrators to hire and retain the IPs capable of developing user-centered services in academic libraries. Originality/value: Practical suggestions made for hiring, retaining and developing IPs in academic libraries would be beneficial for other developing countries with similar context. It addressed an unexplored area in the context of a developing country and reported original research that will assist policy and decision-makers to hire and retain competent human resources.